Convergence and tensions in Geography teachers initial education: initial teacher education - debates (Olhar de Professor, 2011)
This article presents the debate about the initial education of Geography teachers and the tensions between the academia and the cultural scientific institutions related to this area of study and also to schools from basic education and the questions raised by these formative institutions about some public policies. Do Geography courses, either teaching or bachelor degrees contribute to the education of future teachers by means of a solid curriculum that provides a sound knowledge about Geography? Can the research methods and techniques be used during the teaching practice and later in the future profession? Are the relations between the university and the schools where the teaching practice takes place articulated in terms of teaching knowledge and the early years of teaching? Do the public schools have projects with proper human and material resources so that they can contribute to the formative activities of future Geography teachers? These are the main issues discussed in the article and in debates illuminated by Geography and Education researchers.
Keywords: Geography teacher initial education. Research as a formative principle. Teaching practice. Public school. Curricular proposals.